Biomedical Applications of Bisphosphonate Chelating Agents by Metal Cations as Drug Design for Prevention and Treatment of Osteoporosis using QM/MM Method - (:unkn) unknown (AMG Transcend Association, 2022)
By investigating their pharmacological activity, bisphosphonate drugs can be employed to prevent the loss of one density and treat bone diseases like osteoporosis. The capability of bisphosphonates is to be stuck and be kept within bone during osteoclast-mediated bone inorganic material decomposition. The main problem accompanied by their application is their low oral bioavailability. Several delivery systems, such as metal chelating, nanoparticles, and contrast agents, have been selected to modify their absorption and to conduct them to sites other than bone cells. In this contribution, we have investigated the pharmacological and clinical application of bisphosphonate drugs of 5AFX, 4QPF, 3DYG, 2I19, and 2F92 using novel QM/MM applications of DFT, MC, and MD due to physicochemical properties of NMR, charge transfer, Gibbs free energy, electronic-kinetic and nuclear repulse energies in the pharmaceutical and biomedical fields. The bisphosphonate agent has been accomplished in chelation with the metal cation of Mg2+ and Cu2+ through the PDB structures of 5AFX, 4QPF, 3DYG, 2I19, and 2F92 drugs. Since the metal binding of phosphonate groups is relatively bulky, with six oxygens having a negative charge more than pH= 4, which is high (approximately four per ligand), these structures are active in forming the chelated compounds through the drug design method. The connection between structure and activity methods play an important role in predicting the biological properties of target compounds and their physicochemical properties. In this article, Ramachandran plot in drug design has played an efficient function in target identification and designing novel drugs for exploring the parameters of amino acid sequence, molecular modeling, and the 3-D structure bisphosphonate agents of novel drugs of 5AFX, 4QPF, 3DYG, 2I19, and 2F92.